Equity Market Timing dan Struktur Modal - Nidya Fahima; Sri Maemunah Soeharto; Chorry Sulistyowati (Jurnal Manajemen Teori dan Terapan | Journal of Theory and Applied Management, 2016)
This study is an empirical testing of equity market timing and capital structure at firms which are doing IPO 2001 and 2002. The aims of this study are to test about the effect of equity market timing to capital structure and to test the persistency of the effect of equity market timing to firm’s capital structure in Indonesia. This study also used control variable, that asset tangibility, size and profitability. To analyze the data, this study used multiple regressions with SPSS 16.0 to test independent and dependent variables. The result suggest that the equity market timing has not significantly negative effect to the firms’ capital structure which used IPO 2001 and 2002 that are listed in BEI, and the effect of equity market timing to the firms’ capital structure are not persistent that the negative effect of equity market timing to the firms’ capital structure disappear within third years after IPO.